2014
DOI: 10.1089/gyn.2012.0142
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Morbid Obesity on Surgical Outcomes in Robotic-Assisted Gynecologic Surgery

Abstract: Objective: The aim of this research was to estimate the impact of body mass index (BMI) on surgical outcomes in patients undergoing robotic-assisted gynecologic surgery. Materials and Methods: This study was a retrospective review of prospectively collected cohort data for a consecutive series of patients undergoing gynecologic robotic surgery in a single institution. BMI, expressed as kg/m 2 , was abstracted from the medical charts of all patients undergoing robotic hysterectomy. Data on estimated blood loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 21 publications
1
14
1
1
Order By: Relevance
“… 45.8 (41–52) 36.9 (28–48) 109± 207 (100–350) 1.4± 141± Almeida et al [ 41 ] PS 4 2011–2012 Benign 12 TLH Robot 44.4 (40–59) 44.1 (28–67) 109.6± 146.3± 1 (1–2) 259± Bernardini et al [ 42 ] a PS 4 2008–2010 Malign (mixed) 45 TLH Robot 40.3 (35–75) 61 (36–87) 270 (135–470) 200 (50–1500) 2 (1–24) NA (–) Bijen et al [ 8 ] a RCT 2b 2007–2009 Malign (no LND) 31 TLH Conv. NA (35–55) NA (–) NA (–) NA (–) NA (–) NA (–) Eddib et al [ 43 ] RS 4 2010–2012 Both (mixed LND) 84 TLH Robot 42.5± 50.4± 215.1± 79.3± …”
Section: Resultsmentioning
confidence: 99%
“… 45.8 (41–52) 36.9 (28–48) 109± 207 (100–350) 1.4± 141± Almeida et al [ 41 ] PS 4 2011–2012 Benign 12 TLH Robot 44.4 (40–59) 44.1 (28–67) 109.6± 146.3± 1 (1–2) 259± Bernardini et al [ 42 ] a PS 4 2008–2010 Malign (mixed) 45 TLH Robot 40.3 (35–75) 61 (36–87) 270 (135–470) 200 (50–1500) 2 (1–24) NA (–) Bijen et al [ 8 ] a RCT 2b 2007–2009 Malign (no LND) 31 TLH Conv. NA (35–55) NA (–) NA (–) NA (–) NA (–) NA (–) Eddib et al [ 43 ] RS 4 2010–2012 Both (mixed LND) 84 TLH Robot 42.5± 50.4± 215.1± 79.3± …”
Section: Resultsmentioning
confidence: 99%
“…The authors reported similar results and concluded that RAH was feasible but required training and special expertise. Another study by Eddib et al ( 28 ) examined the impact of BMI on surgical outcomes of RAH. They concluded that procedure time was longer in morbidly obese patients; however, obesity had no impact on other outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These results for robotic hysterectomy are in accordance with another study, in which patients classified as morbidly obese showed higher operative times than those who were not (BMI < 35). 17 No correlation between uterine weight and operative time has been shown in the literature. 18,19 In agreement to that, no correlation between the total operative time and the uterine weight, or between the total operative time and the number of previous abdominal surgeries was observed in the present study.…”
Section: Discussionmentioning
confidence: 99%